High day-to-day repeatability of lower extremity muscle activation patterns and joint biomechanics of dual-belt treadmill gait: A reliability study in healthy young adults. (April 2020) - Rutherford, Derek James; Moyer, Rebecca; Baker, Matthew; Saleh, Sara
Abstract: Purpose: The reliability of lower extremity muscle activation patterns has not been clearly studied in a dual-belt instrumented treadmill environment. The primary study objective was to quantify the day-to-day reliability of quadriceps, hamstrings, gastrocnemius and gluteus medius activation patterns in healthy young adult gait. Secondarily, the reliability of spatiotemporal, and knee/hip motion and moment-based gait outcomes was assessed. Scope: 20 young adults were recruited and tested on two separate days. Using standardized procedures, participants were prepared for surface electromyography and lower extremity motion capture. All individuals walked on a dual-belt instrumented treadmill while muscle activation, segment motions and ground reaction forces were recorded. Sagittal plane motion and net external sagittal and frontal plane moments were calculated. Discrete biomechanical and muscle activation measures were calculated, and non-negative matrix factorization extracted amplitude and temporal muscle activation features. Intraclass Correlation Coefficients, Standard Error of Measurement and Minimum Detectable Change were calculated. Conclusions: High to excellent Intraclass correlation coefficients were found between visits for most primary and secondary outcomes. The absolute and relative reliability, including Minimum Detectable Change values, provided in this study support the use of dual-belt instrumented treadmill walking as an acceptable medium to collect biomechanical and lower extremity EMG outcomes for future studies.